The T-box transcription factor Eomesodermin governs haemogenic competence of yolk sac mesodermal progenitors - Harland, LTG; Simon, CS; Senft, AD; Costello, I; Greder, L; Imaz-Rosshandler, I; Göttgens, B; Marioni, JC; Bikoff, EK; Porcher, C; de Bruijn, MFTR; Robertson, EJ (Springer Nature, 2021)
Extra-embryonic mesoderm (ExM)-composed of the earliest cells that traverse the primitive streak-gives rise to the endothelium as well as haematopoietic progenitors in the developing yolk sac. How a specific subset of ExM becomes committed to a haematopoietic fate remains unclear. Here we demonstrate using an embryonic stem cell model that transient expression of the T-box transcription factor Eomesodermin (Eomes) governs haemogenic competency of ExM. Eomes regulates the accessibility of enhancers that the transcription factor stem cell leukaemia (SCL) normally utilizes to specify primitive erythrocytes and is essential for the normal development of Runx1+ haemogenic endothelium. Single-cell RNA sequencing suggests that Eomes loss of function profoundly blocks the formation of blood progenitors but not specification of Flk-1+ haematoendothelial progenitors. Our findings place Eomes at the top of the transcriptional hierarchy regulating early blood formation and suggest that haemogenic competence is endowed earlier during embryonic development than was previously appreciated.